DRAMA â€œMALAM JAHANAMâ€ KARYA MOTINGGO BUSYE: SEBUAH TELAAH PSIKOLOGIS - Hamdani, Agus (Jurnal Pendidikan Bahasa dan Sastra, 2016)
Abstract This article summarizes the results of research that seeks to dismantle the psychological side of the main characters in the drama Hell Night work is Motinggo Busye.Melalui study analysis shows that the main character of this drama named Soleman have a picture of physical and non-physical round. Factors that influence personality Soleman are internal and external factors. Internal factors such as congenital inherited from his father. External factors such as the bitter life experiences Apart from families poor moral, environmental conditions also provide opportunities for Soleman for having an affair with the wife of the lain.Secara indirectly, Soleman personality in the drama that reinforces the opinion of the middle of two opposite schools of psychology (nativism and empiricism), that a person's personality is basically influenced by two factors simultaneously, which is a factor in (hereditary) and external (environmental). Keywords: drama, psychological study, psychology literature.